First record of Macrovalsaria megalospora (Dothideomycetes-Ascomycota) from Colombia - Raymundo, Tania; Martínez Pineda, Michelle; Osorio-Navarro, Yulena S.; Chamorro-Martínez, Hannya A.; Valenzuela Garza, Ricardo (Instituto de Ecología, A.C., 2020)
Background and Aims: Macrovalsaria is a monotypic genus of Dothideomycetes, widely cited from tropical and dry regions in Africa, Asia and Australia. In America it has only been described from French Guiana and Mexico; therefore, this study aims to describe Macrovalsaria megalospora for the first time from Colombia. Methods: The specimens were collected in the Caribbean region of Colombia; simultaneously, the hosts on which they grew were registered, and they were described and identified according to the traditional techniques in mycology. In addition, the spores were observed with the scanning electron microscope. The material is deposited in the fungus collection of the ENCB and HEUS herbaria, of the Escuela Nacional de Ciencias Biológicas of the Instituto Politécnico Nacional in Mexico and of the Universidad de Sucre in Colombia, respectively. Key results: The description of Macrovalsaria megalospora from Colombia is presented, a species that is characterized by the formation of erumpent pseudothecia, gregarious on dead trees of Ficus americana and Terminalia amazonia. Conclusions: This species is widely distributed in various zones of the Paleotropical region and recently it has been discovered in the Neotropics. However, it is necessary to conduct a phylogenetic revision of the specimens identified as Macrovalsaria megalospora of all tropical regions of the world and confirm that it is a monotypic genus, as well as its importance as a phytopathogen.